2018
DOI: 10.1200/cci.17.00138
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Interventions for Adolescent and Young Adult Cancer Survivors

Abstract: This narrative review describes the evidence regarding digital health interventions targeting adolescent and young adult (AYA) cancer survivors. We reviewed the published literature for studies involving Internet, mHealth, social media, telehealth, and other digital interventions for AYA survivors. We highlight selected studies to illustrate the state of the research in this unique patient population. Interventions have used various digital modalities to improve health behaviors (eg, physical activity, nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 78 publications
2
100
0
2
Order By: Relevance
“…The current review found high levels of positive attitudes and perceptions and few concerns regarding the use of digital health interventions among youth and young adults, consistent with previous investigations that demonstrated acceptability, feasibility, and satisfaction with these approaches across a broad range of outcomes . Similarly, these findings are congruent with a recent review of digital health interventions for AYA cancer survivors, which demonstrated feasibility and acceptability across a broad array of modalities to improve health behaviors and enhance emotional well‐being . Nevertheless, the findings should be considered tentative as they were exploratory in nature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current review found high levels of positive attitudes and perceptions and few concerns regarding the use of digital health interventions among youth and young adults, consistent with previous investigations that demonstrated acceptability, feasibility, and satisfaction with these approaches across a broad range of outcomes . Similarly, these findings are congruent with a recent review of digital health interventions for AYA cancer survivors, which demonstrated feasibility and acceptability across a broad array of modalities to improve health behaviors and enhance emotional well‐being . Nevertheless, the findings should be considered tentative as they were exploratory in nature.…”
Section: Discussionsupporting
confidence: 88%
“…While previous narrative and systematic reviews have reported on digital interventions in AYA cancer patients and survivors, there has not been a systematic review of mHealth and eHealth interventions that spans the continuum of childhood cancer treatment and survivorship, including both youth undergoing cancer treatment and childhood, adolescent, and young adult survivors of childhood cancer. More specifically, a previous narrative review conducted by Devine et al examined digital health interventions targeting AYA cancer survivors . McCann et al conducted a systematic review focused on digital health interventions developed specifically for adolescents and young adults living with or beyond a cancer diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…Technologies were categorised using a previously reported typology 51 : internet (eg, websites, forums, chat rooms and e-tools) (n=9) 13 16 23 26 33–35 37 46 ; social media (dedicated platforms, eg, YouTube, Twitter, Facebook and Instagram) (n=3) 47–49 ; mHealth (eg, mobile phone apps and text messaging) (n=14) 18 19 22 24 28 29 31 39–45 ; telehealth (eg, video conferencing and telephone consultations) (n=1) 17 ; interactive online treatment programmes (n=3) 14 15 50 ; and devices (eg, wearables and other devices/hardware) 25 30 32 (n=3). Five studies involved combinations of technologies.…”
Section: Resultsmentioning
confidence: 99%
“…8 Therefore, it is important for providers to employ appropriate methods of sharing health information, with special attention to the different needs of AYAs treated at pediatric versus adult care facilities, differentiated information needs between AYA patients and caregivers, differing levels of literacy, and preferred type of information. 21,42,43 AYAs can benefit from being educated about the fact that they need to be well informed to provide optimal self-care and management. This in itself is an important developmental goal of older adolescence and emerging adulthood.…”
Section: Evaluating and Sharing Digital Health Informationmentioning
confidence: 99%